Analysis of Attributes in Consumer Preferences towards Rice Purchasing Decisions in South Bangka - Yulia Yulia; Novyandra Ilham Bahtera; Laila Hayati (Universitas Muhammadiyah Palembang, 2024)
Consumer preferences can assist a business in understanding the attributes that are essential or desired by consumers. The decision of a consumer to choose a product is closely related to the preferences of an individual consumer. An example of a commodity in the agricultural sector that has the potential to influence consumer preferences is rice. This study aims to identify the attributes that are preferred by consumers in the decision to purchase rice, considering the importance level of each attribute, in Toboali District, South Bangka Regency. The sampling method used in this research was judgment sampling. Data collection techniques include interviews, questionnaires, observations, and focus group discussions. Data processing in this study uses Conjoint Analysis. The results showed that consumer preferences for rice products were based on certified rice, packaged in sacks, 5 kg in size, and had a tender texture.